Measles outbreak in a tertiary level hospital, Porto, Portugal, 2018: challenges in the post-elimination era - Sá Machado, R. (2019)
A measles outbreak has been occurring in a healthcare setting in Porto, Portugal, since early March 2018, posing public health challenges for a central hospital and the community. Up to 22 April, 96 cases were confirmed, 67 in vaccinated healthcare workers, mostly between 18-39 years old. Following identification of the first cases, control measures were rapidly implemented. Concomitantly, other measles cases were notified in the Northern Region of the country. No common epidemiological link was identified.